Digital Mapping of Forest Fire in Garhwal Himalaya Using Indian Remote Sensing Satellite - Pant, D. N.; Das, K. K.; Roy, P. S. (Indian Forester, 1996)
Forest fires have caused significant damage to the forest ecosystem. The devastating fire which ravaged extensive forest area during the Summer of 1995 in the Western and Central Himalaya drew wide attention of the forest managers and environmentalists. It is essential to evolve a strategy to minimize the damage caused by fire. IRS-IB LISS-II multi-spectral remote sensing data of pre-fire and post-fire period (1993 and 1995) pertaining to district Tehri (U.P) have digitally heen analysed. The supervised classification and digital enhancement approach have been used. The geometrically registercd images have been compared to assess the varying degree of forest fire damage. The total area affected under forest fire has been estimated as 20.58% of the total geographical area. The forest fire affected areas are classified as burnt forest, partially burnt forest and partially burnt fallow/ grassland/scrub land. A real extent ofthese are: 3.82,10.72 and 6.05% respectively. The forest areas identified under smoke plumes have been estimated as 2.96% of total geographical area.